MATHEMATICS EDUCATION BASED ON LOCAL WISDOM: LEARNING STRATEGIES THROUGH HOMBO BATU - Harefa, Darmawan; I Wayan Suastra (Afore : Jurnal Pendidikan Matematika, 2024)
This study aims to explore the application of local wisdom-based mathematics education through learning strategies using the traditional game Hombo Batu. Local wisdom is considered a valuable resource for enriching the learning process and enhancing students' understanding of mathematical concepts. Through this approach, students not only learn theoretically but also connect the material to their daily experiences, which increases their motivation and engagement. The results of the literature review indicate that Hombo Batu can serve as an interactive learning medium, supporting the development of social skills and strengthening students' cultural identity. Although there are challenges in its implementation, such as a lack of training for teachers and limited resources, recommendations for integrating local wisdom into the mathematics education curriculum can help create more meaningful learning experiences. This study is expected to provide insights for the development of more relevant and effective teaching methods in the educational context.